Image of the Main Character and the Value of Character Education in Beranak Beruk Folklore - Prasakti, Angga Warda; Riady, Yasir (LADU: Journal of Languages and Education, 2024)
Background: The position and function of folklore in the last decade seem to have been increasingly shifted due to advances in information technology, cultural systems, social systems and currently developing political systems. It is not impossible that various forms of old culture, including folklore, will be neglected amidst the increasing activity of development and renewal, so it is feared that oral literature which is full of values, norms, and customs will eventually disappear without a trace. Purpose: explaining the image of the character and the value of character education in the story of Beranak Beruk so that it can become a reference in improving character in the world of education. Design and methods: The research method used is qualitative, with data collection techniques through document study and library observation. Results: there are two types of character images in the story Beranak Beruk, there are good images and bad images. Of these two images, only the positive image can be used as a reference for character education values, namely religious, honest, tolerant, disciplined, hard work, creative, independent, democratic, curious, national spirit, love of the country, respect for achievement. , Friendly/Communicative, Loves Peace, Likes Reading, Cares for the Environment, Cares for Social Affairs. Responsibility.